An exploratory study to identify views of students and tutors on effective factors for simulation-based education at the Lisbon School of Medicine - António Velha, Luís Almeida, Madalena Patrício (Revista da Sociedade Portuguesa de Anestesiologia, 2024)
An exploratory study to identify views of students and tutors on effective factors for simulation-based education at the Lisbon School of Medicine